Hypertrophy Training Following A Total Hip Replacement: A Literature Review - Tyson Bull; Andrew Erzen; John O'Donnell; Michael Rafla; David Georgy; Mia Bailey; Amir Takla (North American Sports Medicine Institute, 2024)
Hip OA is becoming more common, with a greater number of younger individuals undergoing total hip arthroplasty (THA). These individuals have the desire to return to considerable loading and in some instances return to sport. The purpose of this review was to investigate the current guidelines and/or protocols for hypertrophy or strengthening in individuals who have undergone total hip arthroplasty. A total of 16 papers were identified, some of which also addressed total knee arthroplasty. There is no consensus for the best practice for a hypertrophy program following THA especially regarding when a direct anterior approach was used during hip arthroplasty. Further research is needed as this is a growing area in rehabilitation. This review aims to bridge the gap by offering a comprehensive synthesis of the available literature on postoperative rehabilitation after THA, with a specific emphasis on identifying the most effective muscular strengthening and hypertrophy training programs for patients undergoing anterior approach hip surgery.